A triaxial tensile machine for three-dimensional membrane components: Experimental investigations and numerical simulations. (February 2018) - Hu, Jianhui; Chen, Wujun; Li, Yipo; Gao, Chengjun; Shi, Taibai; Yang, Deqing
Abstract: The use of fabric materials for inflated membrane structures has attracted considerable attention in recent decades due to light weight, high strength-to-weight ratio and excellent environmental stability. The load curtain of the catenary system for stratospheric membrane structures is a typical three-dimensional component with complex stress state, meaning that existing uniaxial and biaxial machines are not suitable to identify essential mechanical properties of this component. This paper focuses on the development of a new triaxial tensile machine and evaluation of mechanical properties of a three-dimensional load curtain component. The triaxial tensile machine with specific configurations could independently control five loads (X+/X-, Y+/Y- and Z). A series of cyclic experiments are carried out in terms of in-plane and out-of-plane angle combination. It is found that experimental observations in the first cycle and subsequent cycles are distinctly different for three-dimensional membrane components. The force reduction in the first cycle is caused by plastic deformation during loading-unloading process. The stress state in subsequent cycles is approximately elastic due to the elimination of plastic deformation in the first cycle, indicating that cyclic experiments are suitable for identifying stable mechanical properties. The force differences between X+ and X- directions are related to stiffness difference between warp and weft directions. Moreover, the effects of Z force could result in asymmetrical X and Y forces, especially for small out-of-plane angle. Furthermore, a numerical model is developed for comparing with experimental results. The X and Y forces in terms of loading and unloading are in good agreement with experimental results, which could justify numerical methods. Highlights: A novel triaxial tensile machine with specific configurations was proposed. Force reduction in the 1st cycle was caused by the plastic deformation. Quasi-elastic stress state in 3rd cycle was suitable to identify mechanical properties. Force difference (X+/X-) was related to stiffness difference between yarn directions. Z force in a small out-of-plane angle could cause large asymmetrical X and Y forces.